Mad-honey intoxication confirmed by pollen analysis - (:unkn) unknown (INFORMA HEALTHCARE, 2011)
Context. Despite numerous publications showing rhythm disturbance and hypotension caused by mad-honey intoxication, none of the findings are associated with ischemic heart disease. Case details. A 48-year-old patient was admitted to emergency service with acute anterior wall myocardial infarction after ingestion of mad-honey. Stent was implanted to the 99% stenosis lesion in the mid-portion of left anterior descending coronary artery. In this case, pollen analysis showed the suspected honey heavily contaminated with Rhododendron species pollen. Discussion. Mad-honey intoxication cases often apply to emergency service with similar signs and symptoms of acute coronary syndrome

therefore it may cause acute coronary syndrome to be bypassed. This also shows that in the cases of mad-honey intoxication, suspected honey pollen and/or toxin analysis should be done to confirm the diagnosis of mad-honey intoxication.
Keywords: Mad honey; Grayanotoxin; Myocardial infarction